A log modulus and phase angle frequency response calculator program - Escoto, Miguel T., Jr.
This paper describes an interactive program implemented in the basic language. The program was developed on a TRS-80 Model I system but may be executed on any other machine supporting basic with a few minor modifications. The program accepts the transfer function G(S) polynomial in unfactored form by prompting questions on screen then proceeds to calculate the magnitude and phase angle against frequency as parameter. Complex arithmetic is used in the calculations downstream. The points obtained are useful for Bode, Nyquist or Nichols plots, thus characterizing a linear system response to a sinousoidal excitation.
Keywords: Frequency response calculator program